Application of a vine copula for multi-line insurance reserving - Himchan Jeong; Dipak Dey (Risks, 2020)
This article introduces a novel use of the vine copula which captures dependence among multi-line claim triangles, especially when an insurance portfolio consists of more than two lines of business. First, we suggest a way to choose an optimal joint loss development model for multiple lines of business that considers marginal distribution, vine copula structure, and choice of family for each pair of copulas. The performance of the model is also demonstrated with Bayesian model diagnostics and out-of-sample validation measures. Finally, we provide an implication of the dependence modeling, which allows a company to analyze and establish the risk capital for whole portfolio.
Keywords: 330; Bayesian inference; model selection; multi-line reserving; property and casualty insurance; vine copula